Poverty, Tesols's Narratives and "Other Languages": Hermeneutic Tensions in Texting-Researching Practices - Ramanathan, Vaidehi (Archīum Ateneo, 2024)
This brief response addresses concerns raised by Ruanni Tupas in his reading of my book, The English-Vernacular Divide. It provides some background about my study, and attempts to uncover some researching and texting tensions I experienced when writing the book. Straddling as I am different geographic spaces—India and the US—with different discourses regarding English language learning and teaching in each space, the response details how my focus on the local and everyday became a way of showing how some discourses about English (its being a democratizing force, or the language of empowerment) run the risk of turning a blind eye to issues of poverty, access and “other languages, issues that are crucial for TESOL to address.”